Corporate social responsibility for whom? - Mohd Sabrun, Ibrahim; Muhamad, Rusnah (Routledge, 2019)
Corporate social responsibility (CSR) was illuminated by Howard Bowen in 1953 as the fundamental of morality in the discussion of business ethics and social responsibility. CSR describes how a company should behave towards society. The concept of CSR continues to evolve whereby academic researchers and business executives continue to adopt and adapt to the CSR evolution. This chapter provides an analysis concerning for whom is CSR intended. The various classes of stakeholders as found in the literature are discussed. The different sets of institutional contexts are found to influence the classification of stakeholders. The chapter also presents how the extant literature identifies stakeholders. This chapter is helpful in assisting researchers and business executives to understand the needs and demands of the various stakeholders, which is useful for CSR strategic planning.